Semiotics of Color in Omar Abu Risha’s poetry - Abdul-Aziz, Ahmad Ata Allah; Al-Awadi, Mohamed Salem; Al-Thiabat, Muthanna Khalid (Journal of Humanities & Social Sciences, 2021)
This research aims at studying the phenomenon of color in the poetry of Omar Abi Risha, and stating the level of employing such phenomenon in his poetry. Hence, the poet Abu Risha has a unique experience in adopting color as an important element in the artistic formation of his poetry. Therefore, the importance of this research stems from showing the connotations of colors in the poetry of Abu Risha, and showing the aesthetic dimension that such connotations achieve by diving into the depths of words that denote colors, so as to reveal such connotations for the purpose of reaching what is touring in the poet’s Soul, and what he carries in his inner side of hidden meanings. Accordingly, this research deals with Abu Risha’s attitude towards colors and the underlyin semantic purposes that they refer to according to a descriptive and analytical approach. Furthermore, I discovered while doing the research that the poet used colors in his poetry extensively, an in particular red and black colors, which occupied the largest part of his poetic works; in addition to the connotations intended by him by using the expressions indicating colors in his poems, either directly or I directly.